Skrining Fitokimia Sayur Bening Daun Kelor (Moringa Oleifera) - Yopi Suryatim Pratiwi; Sri Handayani; Yesvi Zulfiana (Professional Health Journal, 2023)
Introduction: The mortality rate is an important health indicator and reflects the degree of health in an area. The Infant Mortality Rate (IMR) in Indonesia is still high. The infant mortality rate is largely due to nutritional factors. Some diseases that arise due to malnutrition include pneumonia, diarrhea, and perinatal. Exclusive breastfeeding can reduce infant morbidity and mortality. The most common reason found in breastfeeding mothers who stop breastfeeding is due to insufficient milk production. Utilization of plants/vegetables such as Moringa Oleifera is often used by the community to increase milk production. The most widely used processing of Moringa Oleifera by nursing mothers is to make it a clear vegetable. The aim of this study was to screen for phytochemicals on the clear vegetables of Moringa Oleifera.